Implementación de un modelo para el control de inventario en el almacén, palacio del caucho y accesorios, cantón Quevedo, provincia de Los Ríos año 2013 - Corrales Corrales, Linda Verónica (2015)
This research was developed in the Warehouse Palacio Rubber Accessories of the city of Quevedo, is based theoretically in modern definitions of management and inventory control through a field research developed primarily within the organization could be determined the main problem of the store, is the lack of proper management for the registration and control of their inventories, is lack of policies, procedures, rules and regulations did not allow proper management of their activities, resulting in them losses and losses that affected directly into business results.